Quantitative evaluation of upper limb ataxia in spinocerebellar ataxias. Issue 4 (15th March 2022) - Kishimoto, Yoshiyuki; Hashizume, Atsushi; Imai, Yuta; Nakatochi, Masahiro; Yamada, Shinichiro; Ito, Daisuke; Torii, Ryota; Nagano, Yoshitaka; Fujimoto, Hideo; Katsuno, Masahisa
Abstract: Objective: To quantitatively evaluate upper limb ataxia using a novel pen‐like sensor device in patients with spinocerebellar ataxia (SCA) and to assess its validity, reliability, and sensitivity to disease progression. Methods: We designed a cross‐sectional and longitudinal study of patients with SCA and healthy controls. Upper limb ataxia was evaluated using a device that measures the three‐dimensional position every 10 msec. Participants were instructed to move a pen‐like part of the device iteratively between two buttons. We evaluated the time, length, velocity, and variation coefficient of the stroke, and calculated the distortion index using the mean squared error. The following scales were also evaluated: Scale for the Assessment and Rating of Ataxia (SARA), the International Cooperative Ataxia Rating Scale (ICARS), and the nine‐hole pegboard test. Subjects were followed 12 months after the baseline evaluation. Results: A total of 42 patients with SCA and 33 healthy controls were enrolled and evaluated. For all ataxia indices measured using the device there were significant differences between healthy controls and patients with SCA. Among the ataxia indices, the distortion index showed the strongest correlation with the SARA and ICARS upper limb score (Pearson's r  = 0.647 and 0.722, respectively). Test–retest reliability was high for most of the ataxia indices. In the longitudinal analysis, the distortion index showed high standardized response mean and adjusted effect size, regardless of disease severity. Interpretation: Our study demonstrated that the distortion index is a reliable functional marker that is sensitive to longitudinal change in patients with SCA.